2021
DOI: 10.3390/ijms222111716
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in Humans Activates Pancreatic Stellate Cells via RAGE in Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic stellate cells (PSCs) mainly consist of cancer-associating fibroblasts in pancreatic ductal adenocarcinoma (PDAC). The receptor for advanced glycation end products (RAGE) is implicated in the pathophysiology of diabetic complications. Here, we studied the implication of RAGE in PSC activation in PDAC. The activation of cultured mouse PSCs was evaluated by qPCR. The induction of epithelial mesenchymal transition (EMT) in PDAC cell lines was assessed under stimulation with culture supernatant from act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 57 publications
(73 reference statements)
1
10
0
Order By: Relevance
“…The PDAC tissue is full of stromas as much as 80–90% of the tumor mass, which is mainly related to the proliferation of PSCs. 43 In order to verify this point, the pancreatic cancer tissues and normal adjacent tissues from 14 PDAC patients in Sun Yat-sen Memorial Hospital were collected and stained the proteins of α-SMA, collagen type I, and fibronectin expression related to the stroma matrix by immunohistochemistry. The results suggested that α-SMA, collagen type I, and fibronectin were expressed highly in most PDAC tissues (12/14) and weakly in para -tumor tissues (14/14) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The PDAC tissue is full of stromas as much as 80–90% of the tumor mass, which is mainly related to the proliferation of PSCs. 43 In order to verify this point, the pancreatic cancer tissues and normal adjacent tissues from 14 PDAC patients in Sun Yat-sen Memorial Hospital were collected and stained the proteins of α-SMA, collagen type I, and fibronectin expression related to the stroma matrix by immunohistochemistry. The results suggested that α-SMA, collagen type I, and fibronectin were expressed highly in most PDAC tissues (12/14) and weakly in para -tumor tissues (14/14) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemistry was performed with 4 μm thick sections of paraffin‐embedded tissue specimen as described elsewhere 1 , 20 , 21 . The slides were incubated at 4°C overnight with different primary antibodies shown in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as described previously. 21 The primary antibodies used in this study were shown in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditioned medium of AGE-stimulated PSCs induced epithelial-to-mesenchymal transition (EMT) in human pancreatic cancer cell lines, suggesting that RAGE signaling contributes to the cancer-promoting role of activated PSCs. The ratio of RAGE-positive cells correlated with the degree of α-SMA expression around pancreatic intraepithelial neoplasm, a precancerous lesion, found in surgically resected human pancreatic cancer specimens ( Uchida et al, 2021 ).…”
Section: Metabolic Alterations In Pscsmentioning
confidence: 99%